The Veterinary Profession in Greece. Review of the Present and Prospects for the Future. III. Veterinary Education: A. Schools - ΧΑΤΖΗΟΛΟΣ, ΒΑΣΙΛΕΙΟΣ Κ. (Journal of the Hellenic Veterinary Medical Society, 2019)
The strident advances in science and technology, generally, brought with them new reponsibi lities for improving the quality of education in order to permit ready response to newly created needs and conditions. In Greece, the task of educating aspirants in the veterinary field is carried out by one single institution the Veterinary School at the University of Thessaloniki. Obviously, then, admission to the Veterinary School must, of necessity, be highly selective. A comparison is made herein of the selection process used in Greece with that used in the United States. Remarks are also included on the administration of the Veterinary School in Thessaloniki and on the selection and tenure of faculty members. Some suggestions are put forward for the establishment of a selection process, emphasizing not only the academic achievements of the candidate but also his personal attributes and qualities. Discussed also are various ways for improving the education of the veterinary student, incl tiding revising the molecular level, modernizing text books, and utilizing audiovisual aids and computers. Other matters offered for consideration are the increasing of the required period of educational training to at least six years, as well as the requiring of continuing professional education after graduation in order to enable the veterinarian to remain abreast of new scientific developments and techniques. finally, reference is made to the role of the veterinarian in the American university faculties.¨ as well as to veterinary education in some of the Third World Countries and to the burgeoning need for veterinarians ail over the world.